‘Not Coloured enough’ - Carolus, Samantha Kristen (https://orcid.org/0009-0002-0538-1407) (Rhodes University, 2026)
This practice-based research explores the nuanced intricacies of Coloured identity and Colouredness within the 'Makhanda Coloured community’ in South Africa, Eastern Cape. This research investigates the complexities of identity negotiation in a post-apartheid context by discussing historical, social, and cultural influences through the process of making - included in this submission are three documentaries, a hand-bound book, and a website. Central to this practiced-based research is the locative nature of Coloured identity and Colouredness, highlighting specific characteristics of the ‘Makhanda Coloured communities’ cultural and geographic context. While a large focus of scholarship has focused on Coloured identity in the Western Cape, this research demonstrates how the ‘Makhanda Coloured community’ has specific cultural markers of belonging and authenticity. This practised-based research explores the impact of colonialism, stereotyping and marginalisation on the current-day understanding of Colouredness and Coloured identity. The theme of ‘Not Coloured Enough’ emerges as a site of tension, exploring how boundaries of authenticity and belonging are negotiated within specific Coloured communities and in some instances how they are also rejected in favour of embracing Khoi-San heritage. This practice-based research underscores the dynamic and fluid nature of Colouredness and Coloured identity, which is moulded by history, location, culture and personal agency. This research contributes to understanding the complexities of identity negotiation and belonging within the ‘Makhanda Coloured community’, inviting further discussion on Coloured identity and Colouredness in post-apartheid South Africa through film, writing, photography and bookbinding.
a practice-based exploration of Coloured identity(ies) and ‘Colouredness’ in Makhanda
Keywords: Colored people (South Africa) (http://id.loc.gov/authorities/subjects/sh85028691); Belonging (Social psychology) (http://id.loc.gov/authorities/subjects/sh2010015330); Post-apartheid era (http://id.loc.gov/authorities/subjects/sh2003004073); Stereotypes (Social psychology) (http://id.loc.gov/authorities/subjects/sh85128018); Journalism and Media Studies; Identity negotiation (https://www.wikidata.org/wiki/Q17028966); Authenticity (https://www.wikidata.org/wiki/Q2360032); Cultural depiction (https://www.wikidata.org/wiki/Q20742825)